Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula - Olesen, Jørgen; Meland, Kenneth; Glenner, Henrik; Van Hengstum, Peter J.; Iliffe, Thomas M. (European Journal of Taxonomy, 2017)
A new species belonging to the crustacean class Remipedia is described from an anchialine cave system on the island of Cozumel (Mexico), and is illustrated and compared morphologically and molecularly (CO1 and 16S) with closely related taxa. Xibalbanus cozumelensis sp. nov., the first remipede described from Cozumel, is morphologically similar to Xibalbanus tulumensis (Yager, 1987) from the Yucatán Peninsula, but the two species are genetically separate from each other (about 10% in CO1). A phylogenetic (Bayesian) analysis of Yucatán remipede populations based on CO1 and 16S placed them in a monophyletic Xibalbanus (in Xibalbanidae fam. nov.), with X. cozumelensis as most closely related to X. tulumensis. The Yucatán Peninsula and Cozumel have been separate since approx. early Cenozoic ( 65 Ma), which suggests allopatric speciation for X. cozumelensis sp. nov. and X. tulumensis. However, the comparatively low genetic divergence between the two species may indicate that there has been gene flow between ‘mainland’ Yucatán and Cozumel long after the geological separation of the two landmasses, e.g., in cave systems under the sea bed, either continuously or sporadically, for example during the Last Glacial Maximum when the sea level was about 120 m lower than today.